Atypical Streptococcal Meningitis with Fatal Cerebrovascular Complications: A Case Report - Gabriel D. Pinilla-Monsalve; Daniel F. Torres-Cutiva; Juan P. Fernández-Cubillos (MDPI AG, 2020)
Bacterial meningitis is an infectious pathology that remains a public health challenge. The most frequent etiological agent is Streptococcus pneumoniae, which is also associated with higher rates of mortality and sequels. However, less is known about the clinical presentation of atypical non-pneumoniae streptococcal meningitis. Here, we studied a 23-year-old man with no medical background who presented with projectile vomiting, states of consciousness alteration, unilateral cranial nerve palsy, and meningeal signs. Neuroimaging showed tonsillar herniation, regions of empyema, right transverse and sigmoid sinuses thrombosis, and multiple arterial subcortical infarcts. Cerebrospinal fluid suggested bacterial infection; blood and abscess cultures were positive for Streptococcus constellatus. The patient received antibiotics with no clinical improvement. He deteriorated over the following days, the abolishment of brainstem reflexes was observed, and brain death was declared. Streptococcal meningitis produced by atypical species is a potential cause of lethal cerebrovascular complications, even in immunocompetent patients.